Physical, chemical, and microbiological evaluation of antiaging and antibacterial face serum preparations from gotu kola extracts (Centella asiatica L.) - Latirah, Latirah; Nugroho, Priyanto Dwi (Pharmaciana, 2025)
The amount of air pollution and unhealthy lifestyles can increase the body's free radicals. Gotu kola herb contains asiaticoside, flavonoids, and compounds with antioxidant activity. To evaluation physical, chemical and microbiological formulation serum-gotu kola extract with 10%, 12%, and 14% concentrations. Evaluation concist of organoleptic, physically, chemically, and microbiologically. Organoleptically, the sample had a fresh smell, greenish color, and soft texture, with pH between 5.0-5.5; specific gravity 1.08 g/mL-1.09 g/mL; spreadability 7.0-7.5 cm; stickiness 1.070 more than 2 minutes; viscosity between 1.200-5.100 cP. The antioxidant test DPPH method had an IC50 value 8.79-20.34 ppm, and the FRAP method had an AAE/g of 0.06099-0.08017 mg AAE/g. The phosphomolybdic method had a value of 6.67-23.17 ppm. The antibacterial analysis of serum formulas showed that S. aureus bacteria were more susceptible than E. coli (p<0.05). This indicates that all formulas have more potent inhibition against Gram-positive bacteria. Conclusion The results obtained showed that all formula had antioxidant activity, antimicrobial activity and meets the physical criteria of face serum. Thus the serum formula at a concentration of extract centella 10%, 12%, and 14% can be used to prepare natural serum, which formula 3 (14%) is the best formula.